Bt Cotton adoption and wellbeing of farmers in Pakistan - Nazli, Hina; Orden, David; Sarker, Rakhal; Meilke, Karl (International Food Policy Research Institute, 2012)
Among the four largest cotton-producing countries, only Pakistan had not commercially adopted Bt cotton by 2010. However, the cultivation of first-generation (Cry1Ac) Bt cotton, unapproved and unregulated, increased rapidly after 2005. Using the propensity score matching method, this paper examines the economic impact of the available Bt varieties on farmers’ wellbeing. The analysis is based on data collected through structured questionnaires in January-February 2009 from 206 growers in 16 villages in two cotton-growing districts, Baha-walpur and Mirpur Khas. The results indicate a positive impact of Bt cotton on the wellbeing of farmers in Pakistan. However, the extent of impact varies by agro-climatic conditions and size of farm. Bt cotton appeared most effective in the hot and humid areas where pest pressure from bollworms is high. The per-acre yield gains for medium and large farmers are higher than for small farmers. This suggests that additional public-sector interventions may be complementary to introduction of Bt cotton to make this technology widely beneficial in Pakistan.